Abraham Joshua Heschel: Witness to God in Word and Deed - Merkle, John C. (Studies in Christian-Jewish Relations, 2011)
“There are no proofs for the existence of the God of Abraham,” said Rabbi Abraham Joshua Heschel (1907-1972). “There are only witnesses.” For countless Jews and Christians, Heschel was, in both his words and his deeds, one of the preeminent witnesses to God in the twentieth century. To commemorate the centennial year of his birth, this article presents of a brief overview of Heschel’s inspiring life and works in the service of God.